The Future of Evidence-Based Temperance Interventions - Worthington, Everett L.; van Zyl, Llewellyn E. (Frontiers in Psychology, 2021)
Positive psychology has accumulated a large and ever-growing body of scientific knowledge about human strengths and virtues. However, research on positive psychology interventions (PPIs) to develop such is still in its infancy. In this brief position paper, we summarize the status of PPIs in one of positive psychology’s most important virtues: Temperance. Temperance refers to the capacity to manage habits and protect against excess and is composed of forgiveness, humility, and (we include) patience. Specifically, we examine the current state-of-the-science in the conceptualization of temperance, explore the efficacy of temperance interventions, and reflect upon what the future may hold in this research domain. In this paper, we first highlight the challenges and opportunities for expanding the theoretical conceptualization of temperance and reflect upon the challenges in temperance-related PPIs. For each aspect of temperance, we propose a specific research agenda. Second, we explore what is needed for PPIs to promote temperance and how growth in temperance intervention research can be fostered. Generally, while forgiveness interventions are well-established, we recommended that both humility and patience interventions need more viable evidence-based research on existing and new interventions. Third, we advanced several recommendations regarding how to promote more research in new interventions. These recommendations included attracting more funders to the area, developing new interventions, and employing new technology. Because intervention research in temperance is in its infancy, the future looks rosy for PPI researchers as we move into a second generation of positive psychology research.